THE PROGRAM COMPLEX “LENTA” FOR MODELING OF THE FORMING PROCESS OF THE TAPE, ARMORED BY THE GRID - E. F. Baranovskij; V. A. Pumpur; V. M. Iljushenko (Литьë и металлургия)
In the article there is presented the program complex “LENTA ” for modeling of the armored chlorine-copper tape at continuous casting into rolling crystallizer. There are described the possibilities of the software support and form of representation of the calculation results.